Ways to overcome moral deviations in the education of youth - Rano Ergashevna Yuldasheva (Science and Education, 2022)
In the modern era, the process of inheritance of moral values ​​cannot be considered as something secondary, external in relation to the global manifestations of moral deviations. The development of the moral values ​​of the past is called upon to play an important synthesizing role in the life of society, to harmonize the life of people, to awaken in them feelings of philanthropy.